[tex]\bf 13~~,~~\stackrel{13-4}{9}~~,~~\stackrel{9-4}{5}~~,~~\stackrel{5-4}{1}~~,~~...[/tex]
so as we can see, the "common difference" is -4, namely we're "adding" -4 to get the next term, and the first term is 13.
[tex]\bf n^{th}\textit{ term of an arithmetic sequence}
\\\\
a_n=a_1+(n-1)d\qquad
\begin{cases}
n=n^{th}\ term\\
a_1=\textit{first term's value}\\
d=\textit{common difference}\\
----------\\
d=-4\\
a_1=13\\
n=21
\end{cases}
\\\\\\
\stackrel{general~form}{a_n=13+(n-1)(-4)}
\\\\\\
a_{21}=13+(21-1)(-4)\implies a_{21}=13-80\implies a_{21}=-67[/tex]